2020
DOI: 10.1111/aor.13630
|View full text |Cite
|
Sign up to set email alerts
|

Exploring illness denial of LVAD patients in cardiac rehabilitation and their caregivers: A preliminary study

Abstract: Implantable left ventricular assist devices (LVADs) are increasingly used for patients with heart failure. Despite this evidence, the psychological processes affecting implanted patients and their caregivers are only marginally studied. While common emotional reactions, such as anxiety and depression already receive attention, very little is known about the course of caregiver strain, illness denial, and their reciprocal relation. This preliminary study aims at exploring these critical topics in a cardiac reha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Given that individuals faced similar problems during past epidemics, findings from this study could also be generalized and applied to support people still coping with the negative consequences that previous disease outbreaks had on their mood (i.e., Ebola, SARS, MERS, and tuberculosis) ( Brown and Lees-Haley, 1992 ; Betancourt et al, 2016 ; Huremović, 2019 ; Chew et al, 2020 ). In a broader sense, these results could be extended to relieve the psychological burden of dysfunctional psychological reactions in response to physical and/or psychological illnesses ( Rossi Ferrario and Panzeri, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that individuals faced similar problems during past epidemics, findings from this study could also be generalized and applied to support people still coping with the negative consequences that previous disease outbreaks had on their mood (i.e., Ebola, SARS, MERS, and tuberculosis) ( Brown and Lees-Haley, 1992 ; Betancourt et al, 2016 ; Huremović, 2019 ; Chew et al, 2020 ). In a broader sense, these results could be extended to relieve the psychological burden of dysfunctional psychological reactions in response to physical and/or psychological illnesses ( Rossi Ferrario and Panzeri, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, some of these people may be reluctant to seek professional help due to the associated stigma ( Mannarini et al, 2017b , 2018 , 2020 ; Faccio et al, 2019 ; Mannarini and Rossi, 2019 ). On the other hand, some individuals may deny the problem, leading them to think that it will probably resolve itself naturally ( Sareen et al, 2007 ; Rossi Ferrario et al, 2019 ; Rossi Ferrario and Panzeri, 2020 ), thus choosing to manage the psychological issue on their own ( Wilson and Deane, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The risk is that young people, even after the lockdown implementation, will find themselves even more lost in career construction. Recent studies showed that a large number of young people avoid seeking psychological help (Sareen et al, 2007;Mannarini et al, 2017aMannarini et al, , 2018Mannarini et al, , 2020Mannarini and Rossi, 2019;Rossi and Mannarini, 2019;Rossi Ferrario et al, 2019;Rossi Ferrario and Panzeri, 2020). In this sense, guidance and counseling activities located in universities could play a central role in supporting young people in the recovery after the pandemic.…”
Section: Discussionmentioning
confidence: 99%